2008
DOI: 10.1111/j.1600-0714.2008.00677.x
|View full text |Cite
|
Sign up to set email alerts
|

Histomorphology of healthy oral mucosa in untreated celiac patients: unexpected association with spongiosis

Abstract: Our study showed that the healthy oral mucosa of untreated patients does not reflect the intestinal damage by celiac disease, but it is unexpectedly affected by spongiosis, as being detected for the first time in the literature. This latter feature could be related to gliadin ingestion and could contribute to explain the higher susceptibility of celiac disease patients to suffering from oral mucosa lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
2
4
3
Order By: Relevance
“…These results have been confirmed by a recent study [48] in which no differences were observed in CD3+ count or B-and T-lymphocyte counts, either in the epithelium or the lamina propria of the clinically healthy oral mucosa in untreated CD patients and in controls. This seemed to confirm that the oral mucosa does not reflect the intestinal damage of CD.…”
Section: Role Of the Mouth And Oral Mucosa In CD Studiessupporting
confidence: 81%
See 1 more Smart Citation
“…These results have been confirmed by a recent study [48] in which no differences were observed in CD3+ count or B-and T-lymphocyte counts, either in the epithelium or the lamina propria of the clinically healthy oral mucosa in untreated CD patients and in controls. This seemed to confirm that the oral mucosa does not reflect the intestinal damage of CD.…”
Section: Role Of the Mouth And Oral Mucosa In CD Studiessupporting
confidence: 81%
“…However, the previous observation of consistent inflammatory infiltration of the oral mucosa of CD patients on a GFD led us to hypothesize that an immunological "memory" of gluten hypersensitivity can be created. According to this hypothesis, the same authors [48] evaluated the reaction of oral mucosa to a local gluten challenge [41,42]. They demonstrated that oral supramucosal application and a submucosal injection of gliadin powder or gliadin peptides into patients with treated CD induced significant immunological changes, displayed by an increase in intraepithelial CD4+ T cells, as well as CD4+ and CD8+ T cells in the lamina propria.…”
Section: Role Of the Mouth And Oral Mucosa In CD Studiesmentioning
confidence: 99%
“…The findings from Bardellini et al (27) and other similar observations (29) are however opposed to other recent studies (30,31) which found no differences regarding oral mucosa lymphocyte infiltrate in CD patients when compared with healthy controls. Therefore, more studies similar to the one by Bardellini et al (27) should be performed including larger multi-center cohorts and a blinded comparison of the duodenal and buccal immunohistochemistry analysis to confirm their findings.…”
contrasting
confidence: 77%
“…Recent studies (13,25) have shown no differences regarding the B-and T-lymphocyte (including CD3+) counts, both in the epithelium and in the lamina propria of the oral mucosa of CD patients and controls. However the same studies demonstrated that the oral mucosa was unexpectedly affected by spongiosis, probably linked to a local toxic effect which, in turn, was induced by gluten.…”
Section: Discussionmentioning
confidence: 99%